Comparative analysis of the prevalence of the glutathione S-transferase (GST) system in malignant and benign thyroid tumor cells - Gonçalves, Antonio José (2007)
CONTEXT AND OBJECTIVE: When null, the mu and theta genes of the glutathione S-transferase system (GSTM1 and GSTT1, respectively) are related to malignant tumors affecting the lungs, colon, prostate, bladder and head and neck. In the thyroid, the appearance of cancer has been correlated with deletion of these genes. The aim of this study was to compare the frequencies of these genes in patients with benign and malignant tumors of the thyroid gland. DESIGN AND SETTINGS: This was a cross-sectional clinical trial carried out in the Head and Neck Surgery Division, Faculdade de Medicina da Santa Casa de São Paulo. METHODS: Samples of thyroid tissue were collected from 32 patients and divided into two groups: benign tumor (A) and malignant tumor (B). After DNA extraction, the genes were amplifi ed using PCR. RESULTS: The B group presented four cases of positive genotyping for both genes, seven positive for GSTT1 and negative for GSTM1, two negative for GSTT1 and positive for GSTM1, and only one case of double negative. The A group showed 11 cases with positive genotyping for both genes and none with the double negative genotype. CONCLUSION: In this study, there was no relationship between the presence of the GSTT1 and GSTM1 genes and the benign and malignant thyroid tumors.